Biology, Flowering and Fruiting of the Cactus Opuntia spp.: A Review and Some Observations on Three Varieties in Morocco - Arba,Mohamed (2017)
ABSTRACT The cactus is a succulent plant resistant to droughts. According to the recently reviewed classification, cacti belong to the family of Opuntiaceae Desv. (synon. Cactaceae Juss.) with Opuntia Mill. as the typical genus. This genus is economically the most important in the family, as it includes a group of cactus pear plants which play an important role in the agricultural systems of arid and semi-arid regions. Flowering of the cactus pear fruit is an important determinant of the fruit harvesting period. The goal of this paper is to present the physiology of the cactus pear and to explain in detail the biology of its flowering and fruiting processes. This study is also enriched by our observations on the flowering and fruiting of three varieties of cactus pear that we followed for two successive years in southern Morocco.